Pengembangan Media Pembelajaran PAI dan Budi Pekerti Berbasis Powtoon Materi Kejujuran Kelas 2 SD - Ridaul Maghfiroh; Aditya Dwi Saputro; Adhi Setiyawan; Asniyah Nailasariy (IAIN PAREPARE, 2023)
This research focuses on exploring the use of the Powtoon application as a means of developing effective learning media to improve PAI and children's ethics. This study aims to examine the impact of using learning media using the Powtoon application on learning outcomes and understanding and moral development of children. This type of research is research and development (R&D). Research and development is a process or method used to validate and develop a product. The product developed in this study is a learning media using Powtoon in PAI and Ethics. The development of learning media using the Powtoon application can increase the effectiveness of children's moral learning. In the research conducted, the use of learning media such as videos and animations made using the Powtoon application has a positive effect on increasing students' understanding and interest in moral subjects. In this article, we will discuss several important points, namely the process of developing PAI and Ethics learning media using the Powtoon application for children, the response of teachers and students to the development of learning media using the Powtoon application in PAI and children's Ethics, the role of learning media developed using the Powtoon application in increasing students' understanding of the concepts of PAI and Ethics. Keywords: Learning Media, Powtoon, PAI and Child Ethics